Pengembangan Wayang Digital Untuk Menguatkan Karakter Cinta Budaya Daerah Pada Anak Usia Dini - Fahad Ainun Najib; Nurbiana Dhieni; Nurjannah (Jurnal Pendidikan Anak Usia Dini Undiksha, 2023)
The unlimited exchange of information, culture, and art between countries causes cultural acculturation, which causes the loss of a culture in a country; one of the arts that are starting to be forgotten is the original Indonesian art, namely the art of wayang kulit. One of the efforts that can be made to overcome this problem is by utilizing art as a learning medium. Describe the planning and testing of the validity of digital wayang media products. This research belongs to the type of development research using the ADDIE development model. The research subjects were three expert judgments and 8 Kindergarten B children. The data collection in the study was carried out using observation, interview, and questionnaire methods, with the research instrument being a media validity test sheet. The data obtained in the study were analyzed using quantitative descriptive data analysis techniques. The results of the validity test showed that material experts who tested the feasibility of content, indicators, and planning in storyboards obtained a percentage of 75% with proper qualifications, learning media experts obtained a percentage of 96.00% with very decent qualifications, wayang art experts obtained a percentage of 91.60% with qualification is very feasible, field trials obtain a percentage of 83.50% with very good qualifications. Based on the results of this analysis, digital wayang media is very suitable for use in the learning process of early childhood, especially to foster love behavior for regional culture.